Perancangan Interior Pusat Fashion Forever 21 di Surabaya - Anastasia Leony Kristanto; Sriti Mayang Sari (Intra, 2014)
Surabaya is one of the biggest cities in Indonesia. Most people whose life there has a consumptive life style, especially for those women. Surabaya has much fashion retails with its brands and facilities. But it still can’t fulfill what customers needs.So, with this Interior Design Fashion Center “Forever 21” in Surabaya hope can fulfill what customers needs and also can give them a new shopping experience. Forever 21 is a brand which already available in Jakarta and get positive responses from people there. Because the design concept is showing a new and interesting store, and also give a happy atmosphere for customers. This concept ‘ll be applied at display shape and interior element. This project ‘ll be supported with information center, so that people can get information about brand and fashion trend.